The problem in Problem-Based Learning (PBL) - Engku Ibrahim, Engku Haliza (2008)
Designing a problem that can meet the course objectives is an essential ingredient in the success of a pbl classroom. While many admit that pbl offer many advantages in terms of encouraging learner autonomy, active learner participation and involvement in their own learning processes, constraints of time frequently deter practitioners from choosing pbl.